An Analysis of Students Vocabulary in Using Antonyms of the Second Years Students at SMP Negeri 05 Tambusai - Caniago, Aminah; Rahayu, Pipit; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was descriptive qualitative, the kind of this research had purpose to make describe aboutsituation with objective. This research was done with some steps collected the data, analyzed the data, madeconclusion, and report. Based on the analyzed the data which by researcher, that skill of second years students ofSMP Negeri 5 Tambusai was Very Poor category and frequency were 10% of the students very poor category, poor category 7%, fair level with the percentage 12%. So, it can be concluded that the students of second years was fairlevel of vocabulary in antonyms.